A Framework for Cloud-Based Healthcare Services to Monitor Noncommunicable Diseases Patient. (5th March 2015) - Al-Qurishi, Muhammad; Al-Rakhami, Mabrook; Al-Qershi, Fattoh; Hassan, Mohammad Mehedi; Alamri, Atif; Khan, Hameed Ullah; Xiang, Yang
Abstract : Monitoring patients who have noncommunicable diseases is a big challenge. These illnesses require a continuous monitoring that leads to high cost for patients' healthcare. Several solutions proposed reducing the impact of these diseases in terms of economic with respect to quality of services. One of the best solutions is mobile healthcare, where patients do not need to be hospitalized under supervision of caregivers. This paper presents a new hybrid framework based on mobile multimedia cloud that is scalable and efficient and provides cost-effective monitoring solution for noncommunicable disease patient. In order to validate the effectiveness of the framework, we also propose a novel evaluation model based on Analytical Hierarchy Process (AHP), which incorporates some criteria from multiple decision makers in the context of healthcare monitoring applications. Using the proposed evaluation model, we analyzed three possible frameworks (proposed hybrid framework, mobile, and multimedia frameworks) in terms of their applicability in the real healthcare environment.